Additions to Macgarvieomyces in Iran: Morphological and Phylogenetic Analyses Reveal Six New Species - Abdollah Ahmadpour; Youbert Ghosta; Fatemeh Alavi; Zahra Alavi; Esmaeil Hashemlou; Jaturong Kumla; Samantha C. Karunarathna; Nakarin Suwannarach (Journal of Fungi, 2025)
The genus Macgarvieomyces (Magnaporthales, Sordariomycetes, Ascomycota) currently includes three species, which are associated with leaf spots on plants belonging to the Cyperaceae and Juncaceae families and are known only in Europe and New Zealand. During a comprehensive survey conducted between 2020 and 2022 targeting host plants from these families across various regions of Iran, six novel species of Macgarvieomyces—M. caspica, M. cyperi, M. junci-acuti, M. juncigenus, M. salkadehensis, and M. schoeni—were uncovered. These species were identified based on detailed morphological characterizations and multi-locus phylogenetic analyses using ITS-rDNA, RPB1, ACT, and CAL gene regions. This study provides thorough descriptions and illustrations of the new taxa, including information on their morphology, ecological preferences, and geographic distribution. The phylogenetic relationships among the species are also discussed. This work significantly enhances the known diversity of Macgarvieomyces associated with Cyperaceae and Juncaceae, expands their geographic distribution, and underscores the value of integrating morphological and molecular data in fungal taxonomy; accordingly, the findings of this study lay the groundwork for future ecological and evolutionary studies of this genus.